Synthesis of glycosylated β3-homo-threonine conjugates for mucin-like glycopeptide antigen analogues - Karch, Florian; Hoffmann-Röder, Anja (Beilstein Journal of Organic Chemistry, 2010)
Glycopeptides from the mucin family decorated with tumour-associated carbohydrate antigens (TACA) have proven to be important target structures for the development of molecularly defined anti-cancer vaccines. The strategic incorporation of β-amino acid building blocks into such mucin-type sequences offers the potential to create pseudo-glycopeptide antigens with improved bioavailability for tumour immunotherapy. Towards this end, TN and TF antigen conjugates O-glycosidically linked to Fmoc-β3-homo-threonine were prepared in good yield via Arndt–Eistert homologation of the corresponding glycosyl α-amino acid derivative. By incorporation of TN-Fmoc-β3hThr conjugate into the 20 amino acid tandem repeat sequence of MUC1 using sequential solid-phase glycopeptide synthesis, a first example of a mixed α/β-hybrid glycopeptide building block was obtained. The latter is of interest for the development of novel glycoconjugate mimics and model structures for anti-cancer vaccines with increased biological half-life.
Keywords: glycopeptide; glycosylamino acids; β3-homo-threonine; MUC1 antigens; solid-phase synthesis